A viral necrosome mediates direct RIPK3 activation to promote inflammatory necroptosis - Shufen Li; Hao Li; Zhenxing Zhou; Meidi Ye; Yifei Wang; Wenqin Li; Zhenqiong Guan; Zihan Guan; Chongtao Zhang; Yulan Zhang; Wei Liu; Ke Peng (Proceedings of the National Academy of Sciences, 2025)
Necroptosis is an inflammatory programmed cell death pathway triggered by RIPK3 activation through one of the upstream RHIM-domain-containing proteins including RIPK1, TRIF, and ZBP1. Whether necroptosis can be activated independent of the upstream signaling pathways leading to inflammatory pathogenesis remains ambiguous. Here, we revealed a mechanism in which a viral protein mediates direct RIPK3 activation resulting in severe inflammatory pathogenesis in patients. The nonstructural protein NSs of a pathogenic hemorrhagic virus, SFTSV, interacts with the RIPK3 kinase domain and forms biocondensate to promote RIPK3 autophosphorylation and necroptosis activation in an RHIM-independent manner. In parallel, sequestration of RIPK3 within the NSs–RIPK3 condensate inhibited RIPK3-mediated apoptosis and promoted viral replication. Infection with an SFTSV NSs mutant virus not forming NSs condensate triggered pronounced apoptosis resulting in reduced viral replication and decreased fatality in vivo. Blocking SFTSV-triggered necroptosis through depletion of MLKL or treatment with a RIPK3-kinase inhibitor reduced viral inflammatory pathogenesis and fatality in vivo. In contrast, blocking SFTSV-triggered apoptosis through depletion of RIPK3 resulted in enhanced viral replication and increased fatality in vivo. The virus-triggered necroptosis correlated with severe inflammatory pathogenesis and lethality in virus-infected patients. The NSs–RIPK3 condensate may represent a necroptosis activation mechanism that promotes viral pathogenesis.